Tele-Yoga in Long Term Illness–Protocol for a Randomised Controlled Trial Including a Process Evaluation and Results from a Pilot Study - Anna Strömberg (MDPI AG, 2021)
Background: For people with long-term illness, debilitated by severe symptoms, it can be difficult to attend regular yoga classes. We have therefore developed a tele-health format of yoga that can be delivered in the home. The tele-yoga was co-designed with members of a patient-organisation, yoga-instructor, and IT-technician. It includes live-streamed group-yoga sessions twice a week and an app with instructions on how to self-perform yoga. Aim: To describe a study protocol for a randomised controlled trial (RCT) including a process evaluation and report on a pilot study evaluating method- and intervention-related components including feasibility, safety, and efficacy. Methods: Ten participants with heart failure aged between 41–76 years were randomised to tele-yoga (n = 5) or to the control group (n = 5). In the pilot study recruitment, enrolment, randomisation, and data collection of all outcomes including primary, secondary and process evaluation measures were tested according to the study protocol. Fidelity, adherence and acceptability to the tele-yoga group training and app use was determined. Safety was assessed by adverse events. Results: The pilot revealed that the methodological aspect of the protocol worked sufficiently in all aspects except for missing data in the physical test of two participants and one participant in the control-group that dropped out of the study at three months follow-up. The tele-yoga training did not lead to any adverse events or injuries, adherence of tele-yoga was sufficient according to preset limits. The tele-yoga intervention also showed some favourable trends of improvements in the composite-end point compared to the active control group. However, since data only was presented descriptively due to the small sample size, the impact of these trends should be interpreted carefully. Conclusion: Our pilot study showed promising results in feasibility, safety, and acceptability of the tele-yoga intervention. Some changes in the protocol have been made to decrease the risk of missing data in the measures of physical function and in the full-scale RCT now ongoing the results of the sample size calculation for 300 participants have included the estimated level of drop outs and missing data.